Collective negative shocks and preferences for redistribution: Evidence from the COVID-19 crisis in Germany - Luna Bellani; Andrea Fazio; Francesco Scervini (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2022)
Using new data from a three-wave panel survey administered in Germany between May 2020 and May 2021, this paper studies the impact of a negative shock affecting every strata of the population, such as the development of COVID-19, on preferences for redistribution. Exploiting the plausibly exogenous change in severity of the infection rate at the county level, we show that, contrary to some theoretical expectations, the worse the crisis, the lower the support for redistribution of our respondents. We provide further suggestive evidence that this is not driven by a decrease in inequality aversion, but this might be the result of a decrease in trust in the institutions who are in charge of redistributive policies.
urn:nbn:de:bsz:352-2-1efbsn24s1qet1
Keywords: D31; D63; D72; 320; preferences for redistribution; inequality aversion; COVID-19